Association Between Dietary Inflammatory Index and Heart Failure: Results From NHANES (1999–2018) - Liu, Zuheng; Liu, Haiyue; Deng, Qinsheng; Sun, Changqing; He, Wangwei; Zheng, Wuyang; Tang, Rong; Li, Weihua; Xie, Qiang (Frontiers in Cardiovascular Medicine, 2021)
Objective: To explore the relationship between dietary inflammatory index (DII) and heart failure (HF) in participants with cardiovascular and cerebrovascular diseases. Methods: NHANES (1998-2018) data were collected and used to assess the association of HF with DII. Twenty-four-hour dietary consumptions were used to calculate the scores of DII. Demographic characteristics, physical and laboratory examinations were collected for the comparison between heart failure and non-HF groups. Logistic regression analysis and random forest analysis were performed to calculate the odds rate and determined the potential beneficial diet components in HF. Results: 19067 cardiac-cerebral vascular disease participants were categorized as HF (n = 1382, 7.25%) and non-HF (n = 17685, 92.75%) groups. HF participants had higher levels of DII score compared with non-HF group (0.239 ± 1.702 vs. -0.145 ± 1.704, p < 0.001). Compared with individuals with T1 (DII: -3.884 to -0.570) of DII, those in T3 (DII: 1.019 to 4.598) had higher level of total cholesterol (4.49 ± 1.16 mmol/L vs. 4.75 ± 1.28 mmol/L, p < 0.01), globulin (29.92 ± 5.37 g/L vs. 31.29 ± 5.84 g/L, p < 0.001) and pulse rate (69.90 ± 12.22 vs. 72.22 ± 12.77, p < 0.001), and lower levels of albumin (40.76 ± 3.52 g/L vs. 39.86 ± 3.83 g/L, p < 0.001), hemoglobin (13.76 ± 1.65 g/dL vs. 13.46 ± 1.77 g/dL, p < 0.05) and hematocrit (40.83 ± 4.69% vs. 40.17 ± 5.01%, p < 0.05). The odds rates of HF for DII from logistic regression were 1.140, 1.158 and 1.110 in model 1, 2 and 3, respectively. In addition, from the results of random forest analysis, dietary magnesium, fiber and beta carotene may be essential in HF. Conclusion: DII was positively associated with HF in US adults, and dietary intervention might be a promising method in the therapy of HF.